Psychological Support of the Development of the Rehabilitation Potential of Employees of the Force - Sheviakov, Oleksii; Slavska, Yanina; Cherednichenko, Oleksii (Scientific Center of Innovative Research OÜ, Estonia, 2024)
ENG: The article the main approaches to the psychological support of the process of development of rehabilitation potential of specialists of law enforcement agencies. The purpose of our article is to study the peculiarities of social functioning and the leading factors of mental trauma in specialists of law enforcement agencies with depressive disorders of neurotic origin. During the research, the following methods were used: analysis of special, scientific and methodological literature, analysis of documentary materials, observation, testing, experiment, methods of mathematical statistics. Factors of development of rehabilitation potential of personality are characterized. The peculiarities of the systemic structure of mental phenomena and the concept of psychological support of the process of development of rehabilitation potential are considered. The need to implement a systematic approach based on empirical data, which includes research aimed at harmonizing the psychological state of law enforcement officers, is emphasized. Empirical research has revealed the peculiarities of the social functioning of specialists in law enforcement agencies with depressive disorders of neurotic origin. There are differences in the psychological well- being of professionals with depressive disorders of neurotic origin and people without mental disorders, namely: people without mental disorders are characterized by a predominance of interest in life, reflecting their interest in everyday life, enthusiasm for what is happening; in people with mental disorders, the indicators of "consistency in achieving goals" and "consistency between goals and their achievement" are such that indicate inadequate assessment and inability to use their own strength to achieve the goal.
O. Sheviakov: ORCID 0000-0001-8348-1935; Ya. Slavska: ORCID 0000-0003-2498-3323; O. Cherednichenko: ORCID 0000-0002-0423-2402
Keywords: rehabilitation potential; psychological state; specialists of law enforcement agencies; development; methodological approach; social support; psychological support; КФОП; SOCIAL SCIENCES; SOCIAL SCIENCES::Social sciences; SOCIAL SCIENCES::Social sciences::Psychology